Evaluation of corrective effect of 6 degree of freedom couch on setup errors in intensity modulated radiotherapy for postoperative rectal cancer patients - Xu, Hui; Zhang, Zunhao; Tian, Bo; Li, Xiongfei; Bian, Yunfei; Liang, Xianwei; Bo, Changwen (Frontiers in Oncology, 2023)
Objective: To explore the corrective effect of 6 degree of freedom couch on rotation errors in intensity modulated radiotherapy (IMRT) for postoperative rectal cancer patients, further to probe into the clinical application value of 6 degree of freedom couch in radiotherapy. Methods: From January 1, 2020 to December 1, 2020, 30 patients with rectal cancer receiving postoperative intensity modulated radiotherapy in The First Hospital of Hebei Medical University were included in this retrospective study. The setup error values in all direction of patients before and after 6 degree of freedom correction were collected during each radiotherapy session. Results: In this study, a total of 382 data before and after the correction of 6 degree of freedom couch were collected. We It was found that the setup errors in the Y direction gradually increased, was maximal in the third week, and then became smaller, and the setup errors in the other directions increased with the extension of radiotherapy time and reached the maximum at the 5th week. In the translation direction, the setup errors value in Z direction occurred more frequently than that in X and Y directions between the range of 0.21-0.80 cm. In the rotation direction, the setup errors value in rotation X direction occurred more frequently than that in rotation Y and Z directions between the range of 0.21°-2.99°. In addition, after the correction of the 6 degree of freedom couch in real time, the setup errors in patients were significantly reduced in all directions (P < 0.05). Conclusion: In summary, it was recommended to clinically use 6 degree of freedom couch combined with IMRT for real-time correction of placement errors in patients with rectal cancer undergoing postoperative radiotherapy. At the same time, it was necessary to observe the tumor size and body weight changes of patients on the 5th week. If necessary, radiotherapy positioning and planning should be performed in time.